Clinical transforming of personality disorders: comorbidity, severity or dynamical changes in the structure of individuality?. (February 2022) - Tkachenko, Andrey; Demidova, Liubov; Kirenskaya, Anna; Storozheva, Zinaida; Samylkin, Denis
Abstract : The article is focused on the problems of diagnosis of personality disorders which are solved slightly differently in DSM-5 and ICD-11. It is shown that the current dimensional models are eclectic and do not provide a sufficient explanation of personality disorders, especially their course and dynamical changes. Alternative models of temperament and its neurobiological basis seem to be needed. The alliance between categorical and dimensional approaches is considered as the best way for understanding human personality and the causes of human behavior. The conceptual basis of personality supposes an analysis of personality disorders at different levels, including those which are predominantly based on biology or social influences. The systemic bottom-up and top-down approaches in analysis are considered as promising.